Design and Rationale of a Prospective International Follow-Up Study on Intensive Care Survivors of COVID-19: The Long-Term Impact in Intensive Care Survivors of Coronavirus Disease-19–AFTERCOR - Wildi, Karin; Li Bassi, Gianluigi; Barnett, Adrian; Panigada, Mauro; Colombo, Sebastiano M.; Bandera, Alessandra; Muscatello, Antonio; McNicholas, Bairbre; Laffey, John G.; Battaglini, Denise; Robba, Chiara; Torres, Antoni; et al. (Frontiers in Medicine, 2021)
Background In a disease that has only existed for 18 months, it is difficult to be fully informed of the long-term sequelae of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Evidence is growing that most organ systems can be affected by the virus, causing severe disabilities in survivors. The extent of the aftermath will declare itself over the next 5-10 years, but it is likely to be substantial with profound socio-economic impact on society. Methods This is an international multi-centre, prospective long-term follow-up study of patients who developed severe coronavirus disease-2019 (COVID-19) and were admitted to Intensive Care Units (ICUs). The study will be conducted at international tertiary hospitals. Patients will be monitored from time of ICU discharge up to 24 months. Information will be collected on demographics, co-existing illnesses before ICU admission, severity of illness during ICU admission and post-ICU quality of life as well as organ dysfunction and recovery. Statistical analysis will consist of patient trajectories over time for the key variables of quality of life and organ function. Using latent class analysis, we will determine if there are distinct patterns of patients in terms of recovery. Multivariable regression analyses will be used to examine associations between baseline characteristics and severity variables upon admission and discharge in the ICU, and how these impact outcomes at all follow-up time points up to 2 years. Ethics and dissemination The core study team and local principal investigators will ensure that the study adheres to all relevant national and local regulations, and that the necessary approvals are in place before a site may enroll patients.